A theoretical model of the investors exchange - Eric M. Aldrich; Daniel Friedman (University of California, Economics Department, 2017)
Investors' Exchange LLC (IEX) is a newly approved public exchange that is designed to discourage aggressive high-frequency trading. We explain how IEX differs from traditional continuous double auction markets and present summary data on IEX transactions by trader class and or- der type. Our primary contribution is a simple analytic model of IEX as a constrained version of the continuous double auction. The model predicts that IEX will generally improve price efficiency and lower transactions cost while increasing delay costs. A subset of the model's predictions are testable in the field or in a laboratory environment.
Keywords: C91; D44; D47; D53; G12; G14; 330; Market design; IEX; lab experiments; high-frequency trading; continuous double auction